Book Review: Universities in the Knowledge Society: The Nexus of National Systems of Innovation and Higher Education - Alison Elizabeth Jefferson (Ali Khorsandi Taskoh, 2021)
Author: Timo Aarrevaara, Martin Finkelstein, Glen A. Jones, & Jisun Jung (Eds.) Publisher: Springer Country of Publication: Switzerland Year of Publication: 2021 ISBN: 978-3-030-76578-1 Pages: IX-434